Karateristik Sifat Fisika dan Mekanika Papan Laminasi Kayu Sengon dan Kayu Bayur - Febriana Tri Wulandari; Radjali Amin; Raehanayati Raehanayati (Universitas Negeri Gorontalo, 2022)
Currently, it is increasingly difficult to obtain large and quality sawn timber due to the diminishing supply of wood in natural forests. To overcome this problem, innovation is needed to utilize wood scrap waste as a board product. One form of innovation in the use of wood scrap as a board product is laminated boards. In this study, Sengon and Bayur woods were used which had strong grades III-IV and had specific gravity ranging from 0.29-0.70. Bayur and Sengon wood are suitable to be used as raw materials for laminated boards because they have a light density. The purpose of this research was to determine the physical and mechanical characteristics of laminated boards, the effect of Labur weight, wood species and their interactions. The method used in this study is an experimental method with a factorial completely randomized design (CRD). Characteristics of physical and mechanical properties of laminated boards of Sengon and clothes: density 0.412 gram/cm3; water content 12,459%; thick development 2.019%; thick shrinkage 3.183%; MoE 23031,922 kgf/cm²; MoR 357.208 kgf/cm². Laur weight, type of wood and their interactions have a significant effect on all physical and mechanical properties of Sengon and Bayur laminated boards. The interaction of pumpkin weight and wood species had no significant effect on the water content and MoR tests. Based on the wood strength class, Sengon and Bayur wood laminated boards are classified as class III which can be used as protected heavy construction materials.